Pengaruh Lokasi, Akreditasi dan Biaya Kuliah terhadap Niat Memilih Perguruan Tinggi Swasta di Surabaya - Eli Masnawati; Didit Darmawan (Departement of Mathematics Education, 2023)
Studying the effect of location, accreditation and tuition fees on the intention to choose a private university in Surabaya is the aim of the research being carried out. In Surabaya there are quite a number of private tertiary institutions that compete with each other to generate interest from students. Therefore, it is important to better understand the factors that influence the intention of prospective students to choose a private university in the city. The survey method was used in this study through the distribution of questionnaires given to prospective students and they were considering continuing to higher education. There were 100 high school graduates who were used as respondents. The collected data were analysed using regression analysis to test the relationship between the variables of location, accreditation, and tuition fees with the intention to choose a private college. The results obtained state that the three independent variables in this study are proven to have a real role in generating the intention to have a private university in Surabaya.